Estimating the economic returns to community‐level interventions that build resilience to flooding. Issue 4 (9th September 2020) - Yaron, Gil; Wilson, Dave
Abstract: Flooding is among the largest economic costs of climate change and vulnerable communities in some of the poorest countries are particularly badly affected. Community‐planned interventions to build resilience to floods following climate shocks and stresses play a role in major global development programmes but evidence on their costs and benefits is limited. This paper presents a way of combining evidence from participatory methods to understand changes that have occurred with more formal economic modelling and can be widely used for community‐planned interventions to tackle flooding. We consider projects in flood‐affected communities in Myanmar implemented as part of the Department for International Development‐funded Building Resilience and Adaptation to Climate Extremes and Disasters programme and find estimated economic benefits over a 10‐year period (based on 12–18 months of postintervention data) are significantly greater than estimated costs. The highest returns accrue to relatively small‐scale infrastructure investments planned with communities and local government, drawing on donor finance with community contributions of labour.